Awareness and usage of evidence-based learning strategies among health professions students and faculty. (2nd December 2019) - Piza, Felipe; Kesselheim, Jennifer Cohn; Perzhinsky, Juliette; Drowos, Joanna; Gillis, Roni; Moscovici, Khen; Danciu, Theodora E.; Kosowska, Agnieszka; Gooding, Holly
Abstract: Introduction: Learning is essential and life-long for faculty and students. Often students and teachers use ineffective learning strategies and are not aware of evidence-based strategies. Methods: A multicenter, international, cross-sectional, online survey-based assessment of awareness of evidence-based learning strategies among health professions students ( n  = 679) and faculty ( n  = 205). Results: Students endorsed many study habits which violate evidence-based principles, including studying whatever is due soonest (389/679, 57%), failing to return to course material once a course has ended (465/679, 68%), and re-reading underlined or highlighted notes (298.679, 44%). While the majority of faculty surveyed (125/157, 80%) reported recommending effective study strategies for their students, most students (558/679, 82%) said they did not study the way they do because of instruction from faculty. The majority of faculty (142/156, 91%) and students (347/661, 53%) believe students have different learning styles. Discussion: The results of this study demonstrate health professions students continue to use many ineffective study strategies, and both students and faculty hold misconceptions about evidence-based learning. While planning a curriculum, medical educators should focus on teaching students how to learn and use higher order thinking procedures in addition to teaching content.